Clinical and pathological study of equine babesiosis in draught horses in mosul - G. M. AL-Mola (Iraqi Journal of Veterinary Sciences, 2006)
A total of 128 draught male horses (4-12) years old were used in this study. Among these 100 animals were naturally suffered from babesiosis and 25 clinically normal horses served as control, three dead infected horses served for gross pathological and microscopical changes. Results revealed that diseased horses were affected with the acute form and they exhibited general weakness, loss of appetite, congestion of mucous membranes with petechial hemorrhages in some of them, pale and/or icteric mucous membranes were seen in others, hemoglobinurea, edema of fetlock joint and supraorbital fossa, colic with signs of diarrhea and constipation, profuse sweating, dehydration, rough coat, ticks were observed on various parts of the body. Statistically significant increases were encountered between body temperature, respiratory and heart rates and significant decrease were detected in the RBCS, Hb, PCV, platelets count and fibrinogen. However statistically significant increase were encountered in the sedimentation rate of RBCS, clotting time, prothrombin time and activated partial thromboplastin time. Anemia was macrocytic hypochromic type, the percentage of parasitemia ranged between 6-28 %. Reticulocytes detected in blood smears prepared from blood of diseased animals with mean of 3.07 %. Significant increase WBC count, lymphocytes and significant decrease in neutrophils were showed in diseased animals. The results of biochemical tests revealed significant increase AST, ALT, ALP, total bilirubin, blood urea nitrogen and icteric index with significant decrease in total protein and calcium. The results indicated that equine babesiosis caused gross pathological and microscopical changes in different organs of dead animals.